2010
DOI: 10.1007/s00296-010-1478-2
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of TNFR2, VDR, A2M, GSTT1, GSTM1, and ACE genes with rheumatoid arthritis in South Asians and Caucasians of East Midlands in the United Kingdom

Abstract: Genetic associations of TNFR2, VDR (Bsm I and Fok I), A2M, GSTT(1), GSTM(1) and ACE in South Asian and Caucasian patients with rheumatoid arthritis (RA) were assessed in this study. DNA samples from South Asians (134 cases, 149 controls) and Caucasians (137 cases, 150 controls) from the East Midlands of the United Kingdom were genotyped for seven polymorphisms. All cases were rheumatoid-factor positive. Significant genetic associations were observed with TNFR2 R-R (OR = 3.16, CI 1.20-9.26, P < 0.05), A2M 1-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…30 One eligible study contained data on two different RA groups, and these were treated independently. 21 Thus, a total of 15 separate comparisons met our inclusion criteria. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] These studies comprised five each on psoriasis, vitiligo and RA.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…30 One eligible study contained data on two different RA groups, and these were treated independently. 21 Thus, a total of 15 separate comparisons met our inclusion criteria. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] These studies comprised five each on psoriasis, vitiligo and RA.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22]30 One study was excluded because it contained duplicate data. 30 One eligible study contained data on two different RA groups, and these were treated independently.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[21] Furthermore, it has been demonstrated that in both Caucasian and South Asian populations, the GSTT1 null genotype, but not the GSTM1, is associated with RA. [1] Overall, although some small studies have examined the relationship between the polymorphisms of GSTs and the risk of RA, the association still remains unclear, and the debate continues. The reason for the controversial results of these studies could be associated with the differences in the populations studied and their exposures to agents related to RA development.…”
Section: Discussionmentioning
confidence: 99%
“…Both genetic and environmental factors have been shown to be relevant, contributory factors to the expression and complications of this disease. [1,2] The prevalence of RA is about 1% of the total population, and genetic factors have been estimated to account for 60% of the disease risk. [3] Glutathione S-transferase (GST) genes, known as a superfamily of phase II metabolic enzymes, catalyze the detoxification of xenobiotics via glutathione conjugation.…”
mentioning
confidence: 99%